2016
DOI: 10.1002/ejp.889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the carrier frequency of interferential current on pain modulation and central hypersensitivity in people with chronic nonspecific low back pain: A randomized placebo‐controlled trial

Abstract: These results suggest that although the IFC has changed some physiological mechanisms of pain and showed decrease frequency use of pain medication, there was no change in the primary aim, pain intensity. WHAT DOES THIS STUDY ADD?: The interferential current (IFC) presented advantages in the physiological measures of pain and showed decrease frequency use of pain medication. Future studies should investigate analgesic intake with IFC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 73 publications
(115 reference statements)
2
45
0
3
Order By: Relevance
“…Recently a randomized controlled trial assessed the effect of interferential current on chronic low back pain, but to our knowledge, only one previous trial involving GPs has considered the effect of MT on acute LBP [15, 22]. Curtis et al showed a modest improvement in the Roland-Morris functional scale and patient-assessed functional recovery but no effects on pain intensity, sick leave or overall patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a randomized controlled trial assessed the effect of interferential current on chronic low back pain, but to our knowledge, only one previous trial involving GPs has considered the effect of MT on acute LBP [15, 22]. Curtis et al showed a modest improvement in the Roland-Morris functional scale and patient-assessed functional recovery but no effects on pain intensity, sick leave or overall patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns autores têm demonstrado que o uso de massoterapia pode reduzir a tensão muscular e aliviar processos dolorosos, assim como o que foi observado em nosso estudo (26). O uso isolado de técnicas manuais, quando comparado ao uso de eletroterapia, apresentou-se contraditório em estudos nos quais os efeitos foram observados em pacientes com dor lombar crônica, podendo a CIF ter melhor resposta a curto prazo quanto à funcionalidade e ao controle da dor (27,28), porém a liberação miofascial da musculatura estabilizadora lombar mostrou-se mais adequada para controle da dor lombar (17). Dessa forma, a associação de técnicas manuais com eletroterapia promove efeitos que visam reduzir a dor, podendo estar relacionada à melhora sintomatológica e funcional encontrada no presente estudo.…”
Section: Discussionunclassified
“…Esse resultado demonstra que níveis de depressão podem estar relacionados à presença de um quadro álgico constante e, frente à redução da dor, pode haver, também, uma melhora no quadro depressivo. O uso da CIF é indicado para tratamento de dor lombar crônica, sendo capaz de reduzir a dor e a incapacidade, além de reduzir a frequência do uso de analgésicos (28,41). O uso associado de terapias manuais e CIF podem ser aplicados visando à melhora da mobilidade e da capacidade funcional.…”
Section: Discussionunclassified
“…Interferential current (IC) is an electric current of medium frequency, modulated at low-frequency, capable of penetrating deeper in tissues compared to other low-frequency currents. The guidelines on CLBP treatment mention IC as a non-pharmacological treatment for pain reduction 3 , and may be advantageous in relation to other types of procedures, such as surgery 10,12 . However, they highlight the low evidence level in the studies, suggesting the need for more research related to the topic 1,3,10,11,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…They observed greater analgesia in the IC-treated groups but did not indicate the CF used, only the 0Hz frequency modulation and the treatment time (30 min). Corrêa et al 12 measured the CF analgesic effect between 1 and 4KHz of IC in individuals with CLBP after the first session, after 12 sessions and after 4 months, and saw that IC provided an immediate analgesic effect after the first session, regardless of CF. These two studies show that the 2KHz CF was not used, despite the more satisfactory analgesic results with lower carrier frequencies showed in the literature 10,12 .…”
Section: Introductionmentioning
confidence: 99%